The Impact of Oral‐Systemic Health on Advancing Interprofessional Education Outcomes. Issue 2 (1st February 2017) - Haber, Judith; Hartnett, Erin; Allen, Kenneth; Crowe, Ruth; Adams, Jennifer; Bella, Abigail; Riles, Thomas; Vasilyeva, Anna
Abstract : The aim of this study was to evaluate the effectiveness of an interprofessional education (IPE) clinical simulation and case study experience, using oral‐systemic health as the clinical population health example, for nurse practitioner/midwifery, dental, and medical students' self‐reported attainment of interprofessional competencies. A pretest‐posttest evaluation method was employed, using data from the Interprofessional Collaborative Competency Attainment Scale (ICCAS) completed by two large cohorts of nurse practitioner/midwifery, dental, and medical students at one U.S. university. Data from faculty facilitators were collected to assess their perceptions of the value of exposing students to interprofessional clinical simulation experiences focused on oral‐systemic health. The results showed that self‐reported interprofessional competencies measured by the ICCAS improved significantly from pre‐ to posttest for all three student types in 2013 (p<0.001) and 2014 (p<0.001). Faculty facilitators reported that the IPE clinical simulation experiences were valuable and positively influenced interprofessional communication, collaboration, patient communication, and student understanding of patient care roles. These results suggest that the Teaching Oral‐Systemic Health Program Interprofessional Oral‐Systemic Health Clinical Simulation and Case Study Experience was effective as a standardized, replicable curriculum unit using oral‐systemic health as a population health exemplar to teach and assess interprofessional competencies with nurse practitioner/midwifery, dental, and medical students.